2012
DOI: 10.1590/s1984-70332012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of genotypic values of maize for the agricultural frontier region in northeastern Maranhão, Brazil

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Therefore, the coefficient of determination (R 2 GxE =0.51) confirmed the large participation of the GxE interaction in the phenotypic variance of the genotypes (Table 1). This fact was also shown by the median genotypic correlation between the performances in the various environments (r g(L) =0.31), which results in the complex part of the GxE interaction and causes certain difficulty in the selection of genotypes with a more ample adaptation, as also noted by Arnhold et al (2012) and Mendes et al (2012), in a study on the genotype x environment interaction in corn.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Therefore, the coefficient of determination (R 2 GxE =0.51) confirmed the large participation of the GxE interaction in the phenotypic variance of the genotypes (Table 1). This fact was also shown by the median genotypic correlation between the performances in the various environments (r g(L) =0.31), which results in the complex part of the GxE interaction and causes certain difficulty in the selection of genotypes with a more ample adaptation, as also noted by Arnhold et al (2012) and Mendes et al (2012), in a study on the genotype x environment interaction in corn.…”
Section: Resultsmentioning
confidence: 80%
“…The REML/Blup method for this kind of estimate in the corn crop has been efficiently used in the selection of promising cultivars (Arnhold et al, 2012;Fritsche-Neto et al, 2012;Mendes et al, 2012). In addition, studies developed by Arnhold et al (2012) and Silva et al (2014) show the importance of studying the GxE interaction in the corn-growing regions in Brazil, due to the great diversity of edaphoclimatic conditions in the country, as well as to the diversity of corn cultivars available in the market.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Arnhold et al (2012), analyzing 128 different maize genotypes in two years, reported a correlation of 0.75 between phenotypic and genotypic means using mixed models, showing that the selection based on phenotypic means may not reflect the selection of the same individuals by genotypic means. The same authors also reported that, in occasion of data loss, the mixed models are preferable.…”
Section: Resultsmentioning
confidence: 99%